Frabrication of microlens array in sol-gel glass - Tan, Chee Wee. (2008)
The fabrication of micro lens array pattern using UV contact printing followed by thermal reflow. Soft lithography was used as the technique to transfer the master pattern to optical materials like SU8 and sol-gel.